2014
DOI: 10.13183/jcrg.v3i2.168
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence against Infertile Women

Abstract: Ab s t r a c tPurpose: To investigate the magnitude and patterns of domestic violence among infertile women seeking infertility treatment in Tabriz, north-west of Iran. Methods:A cross-sectional study was conducted with 200 infertile women referred to an infertility center in Tabriz, North-west of Iran, during the year 2013. The women were interviewed using a validated questionnaire for assessment of violence against women. The data were analyzed using SPSS 13 statistical software package mostly providing desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“… 15 , 16 , 18 , 20 , 27 , 28 , 32 35 , 38 , 39 , 43 , 45 , 46 A sub-total of 12 studies with 3,872 participants reported psychological and emotional violence and this type of violence was the most common compared to the rest. 15 , 16 , 20 , 27 , 28 , 30 , 32 35 , 39 , 45 A total of 14 studies with 4,394 participants reported the presence of or increase in physical violence. 15 , 16 , 18 , 20 , 27 , 28 , 30 , 32 35 , 39 , 45 , 46 Also, 11 studies with 3,460 participants reported sexual violence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 15 , 16 , 18 , 20 , 27 , 28 , 32 35 , 38 , 39 , 43 , 45 , 46 A sub-total of 12 studies with 3,872 participants reported psychological and emotional violence and this type of violence was the most common compared to the rest. 15 , 16 , 20 , 27 , 28 , 30 , 32 35 , 39 , 45 A total of 14 studies with 4,394 participants reported the presence of or increase in physical violence. 15 , 16 , 18 , 20 , 27 , 28 , 30 , 32 35 , 39 , 45 , 46 Also, 11 studies with 3,460 participants reported sexual violence.…”
Section: Resultsmentioning
confidence: 99%
“… 15 , 16 , 20 , 27 , 28 , 30 , 32 35 , 39 , 45 A total of 14 studies with 4,394 participants reported the presence of or increase in physical violence. 15 , 16 , 18 , 20 , 27 , 28 , 30 , 32 35 , 39 , 45 , 46 Also, 11 studies with 3,460 participants reported sexual violence. 16 , 18 , 20 , 27 , 28 , 30 , 32 35 , 39 It should be noted that just in one article, only the frequency of different types of violence was separately reported, whereas the total score of violence was not reported.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations